P0874THE IMPACT OF CHRONIC EXPOSURE TO INDOXYL SULFATE ON BONE TURNOVER MARKERS, PTH, VITAMIN D3, AND BIOMECHANICAL AND DENSITOMETRIC PROPERTIES OF BONES IN RAT MODEL. (6th June 2020) - Karbowska, Malgorzata; Sieklucka, Beata; Roszczenko, Alicja; Rogalska, Joanna; Pawlak, Krystyna; Pawlak, Dariusz
Abstract: Background and Aims: Chronic kidney disease (CKD) is a crucial risk factor for biochemical and bone disturbances, as well as non-skeletal calcifications known as Chronic Kidney Disease – Mineral and Bone Disorders (CKD-MBD). Etiopathogenesis of CKD-MBD still remains unknown and arouses much controversy. Indoxyl sulfate (IS) is one of the most potent protein-bound uremic toxin that accumulates during CKD, and exerts aggressive and multidirectional effect on the body. In vitro studies indicate that IS modulates the differentiation and activation of osteoblasts and osteoclasts, however IS impact on bone and mineral disorders still remains unclear. The purpose of the study was to assess IS effect on bone turnover markers, parathyroid hormone (PTH), vitamin D3, and densitometric and biomechanical properties of bones in rat model. Method: Male Wistar rats weighting 180 – 210 g (n=48) were divided into three groups – control group that received pure water and two experimental groups. Experimental groups were exposed to IS in the doses of 100 or 200 mg/kg of b.w. (200 IS) in the drinking water during 4 weeks. At the end of experiment, rats were anesthetized and samples of blood, as well as tibiae, femurs and lumbar spines were collected. Next, the IS bone (cortical and trabecular), plasma and urine levels were determined by high-performance liquid chromatography (HPLC). We also assessed IS influence on bone turnover markers (alkaline phosphatase – ALP, and tartrate-resistant acid phosphatase - TRAP), and level of vitamin D3, and PTH. Furthermore, we evaluated densitometric parameters of tibiae, femurs and lumbar spines using Horizon QDR Series X-ray Bone Densitometer, and performed biomechanical parameters analysis of the cortical bone of the femoral diaphysis using three-point bending test, and the mixed cortico-trabecular structure of the proximal femur by the bending test of the femoral neck. Results: Chronic exposure to IS led to statistically significant increase in plasma, urine, cortical and trabecular bone IS concentrations. We observed reduction in bone turnover markers – bone formation marker ALP in trabecular and cortical bone, and bone resorption marker TRAP in cortical bone. Moreover, the highest dose of IS increased PTH. None of tested IS doses affected vitamin D3 . From data obtained due to biomechanical tests, the highest dose of IS decreased the main indicators of bone strength: yield load (Fy) and displacement at yield [dl(Fy)] of femoral diaphysis and femoral neck, and ultimate load (Fu) and displacement at ultimate [dl(Fu)] of femoral diaphysis. Furthermore, we observed the decrease in elasticity of femoral diaphysis (increased Young's modulus of elasticity E). Additionally, densitometric measurements revealed reduction only in the bone mineral density (BMD) and BMD of diaphyseal area (BMD R2) of tibiae, BMD R2 of femurs in 200 IS group, as well as BMD and BMD R2 of tibiae in 100 IS group. Conclusion: Obtained data confirm that IS affects bones. We observed reduced bone metabolism and strength after exposure to IS. On the basis of the results, we concluded that IS can be one of crucial uremic factors responsible for increased risk of fracture during CKD.